PENGEMBANGAN PROGRAM PEMBINAAN LITERASI MEDIA BAGI SISWA TUNARUNGU - Rina Dwi Kurniawati; Asri Wijiastuti; nFn Yuliyati (Kwangsan: Jurnal Teknologi Pendidikan, 2020)
This study aims to produce a media literacy development program for deaf students in schools. The deaferation behavior of deaf students at school so far has not been able to show their ability to use media as a tool for literacy, learning resources, and there is no follow up after the activity takes place. Media literacy is needed by deaf students because various information can be obtained from technology media. Development of media literacy is done with the aim that students with hearing impairment: (1) are able to utilize the media for positive activities and use media properly and appropriately, and (2) have provision in lifelong learning. The method used is Research & Development (R&D) with 10 stages. Instruments to determine the level of media literacy ability of deaf students and their activeness using daily reading journals are interviews, observation, and documentation. The results showed that media literacy coaching could increase student awareness of using media as a means of literacy. The results of the material validation state that the product developed is "feasible" to be used. Likewise, the results of the validation carried out by special education experts. Instruments for media literacy activities were provided to determine the level of (1) the ability of the media literacy of deaf students, and (2) the use of daily reading journals for the activity of deaf students in literacy activities. From the results of the study, it can be concluded that the media literacy development program is strongly recommended to be applied in every learning with the aim of being able to add to the learning experience of deaf students in collaborating language skills and technology media in each field. ABSTRAKPenelitian ini bertujuan untuk menghasilkan program pembinaan literasi media siswa tunarungu di sekolah. Perilaku berliterasi siswa tunarungu di sekolah sejauh ini belum mampu menunjukkan kemampuannya dalam memanfaatkan media sebagai alat untuk melakukan literasi, sumber belajar, dan belum adanya tindak lanjut setelah kegiatan berlangsung. Literasi media diperlukan siswa tunarungu karena berbagai informasi dapat diperoleh dari media teknologi. Pembinaan literasi media dilakukan dengan tujuan agar siswa tunarungu: (1) mampu memanfaatkan media untuk kegiatan yang bersifat positif dan menggunakan media dengan baik dan tepat, dan (2) memiliki bekal dalam pembelajaran sepanjang hayat. Metode yang digunakan yakni Research & Development (R&D) dengan 10 tahapan. Instrumen untuk mengetahui tingkat kemampuan literasi media siswa tunarungu dan keaktifannya menggunakan jurnal membaca harian adalah wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa pembinaan literasi media mampu meningkatkan kesadaran siswa menggunakan media sebagai sarana literasi. Hasil validasi materi menyatakan bahwa produk yang dikembangkan adalah “layak” digunakan. Demikian juga dengan hasil validasi yang dilakukan oleh ahli pendidikan luar biasa. Instrumen untuk kegiatan literasi media diberikan guna mengetahui tingkat (1) kemampuan literasi media siswa tunarungu, dan (2) penggunaan jurnal membaca harian untuk keaktifan siswa tunarungu dalam kegiatan literasi. Dari hasil penelitian, dapat disimpulkan bahwa program pembinaan literasi media sangat disarankan diterapkan dalam setiap pembelajaran dengan tujuan mampu menambah pengalaman belajar siswa tunarungu dalam mengkolaborasikan keterampilan berbahasa dan media teknologi di setiap bidang.